Conformational Studies with Density Functional Theory of Ethylene Glycol as Intermediate - Shankar Kumar, Ch. Ravi; Varma, M. Chaitanya (Asian Journal of Chemistry, 2017)
Ethylene glycol is an important organic compound and chemical intermediate used in a large number of industrial processes. This study focuses on the density functional theory with basis set 6-311++G(d,p) that provides a method for analyzing the reactivity of ethylene glycol in terms of local and global descriptions that account for various chemical and critical phenomena with optimized structure. A comparative study of these spectroscopic properties was attributed with reported experimental studies justifies the nature of the compound, suitability to act as an intermediate and for conjugation of metallic’s and organics in particular.